Structural and functional analysis of the Rpf2-Rrs1 complex in ribosome biogenesis. Issue 9 (8th April 2015) - Asano, Nozomi; Kato, Koji; Nakamura, Akiyoshi; Komoda, Keisuke; Tanaka, Isao; Yao, Min
Abstract: Proteins Rpf2 and Rrs1 are required for 60S ribosomal subunit maturation. These proteins are necessary for the recruitment of three ribosomal components (5S ribosomal RNA [rRNA], RpL5 and RpL11) to the 90S ribosome precursor and subsequent 27SB pre-rRNA processing. Here we present the crystal structure of the Aspergillus nidulans ( An ) Rpf2-Rrs1 core complex. The core complex contains the tightly interlocked N-terminal domains of Rpf2 and Rrs1. The Rpf2 N-terminal domain includes a Brix domain characterized by similar N- and C-terminal architecture. The long α-helix of Rrs1 joins the C-terminal half of the Brix domain as if it were part of a single molecule. The conserved proline-rich linker connecting the N- and C-terminal domains of Rrs1 wrap around the side of Rpf2 and anchor the C-terminal domain of Rrs1 to a specific site on Rpf2. In addition, gel shift analysis revealed that the Rpf2-Rrs1 complex binds directly to 5S rRNA. Further analysis of Rpf2-Rrs1 mutants demonstrated that Saccharomyces cerevisiae Rpf2 R236 (corresponds to R238 of An Rpf2) plays a significant role in this binding. Based on these studies and previous reports, we have proposed a model for ribosomal component recruitment to the 90S ribosome precursor.